Bacterial pathogen phytosensing in transgenic tobacco and Arabidopsis plants. Issue 1 (2nd November 2012) - Liu, Wusheng; Mazarei, Mitra; Rudis, Mary R.; Fethe, Michael H.; Peng, Yanhui; Millwood, Reginald J.; Schoene, Gisele; Burris, Jason N.; Stewart, C. Neal
Summary Plants are subject to attack by a wide range of phytopathogens. Current pathogen detection methods and technologies are largely constrained to those occurring post‐symptomatically. Recent efforts were made to generate plant sentinels (phytosensors) that can be used for sensing and reporting pathogen contamination in crops. Engineered phytosensors indicating the presence of plant pathogens as early‐warning sentinels potentially have tremendous utility as wide‐area detectors. We previously showed that synthetic promoters containing pathogen and/or defence signalling inducible cis‐acting regulatory elements (RE) fused to a fluorescent protein (FP) reporter could detect phytopathogenic bacteria in a transient phytosensing system. Here, we further advanced this phytosensing system by developing stable transgenic tobacco and Arabidopsis plants containing candidate constructs. The inducibility of each synthetic promoter was examined in response to biotic (bacterial pathogens) or chemical (plant signal molecules salicylic acid, ethylene and methyl jasmonate) treatments using stably transgenic plants. The treated plants were visualized using epifluorescence microscopy and quantified using spectrofluorometry for FP synthesis upon induction. Time‐course analyses of FP synthesis showed that both transgenic tobacco and Arabidopsis plants were capable to respond in predictable ways to pathogen and chemical treatments. These results provide insights into the potential applications of transgenic plants as phytosensors and the implementation of emerging technologies for monitoring plant disease outbreaks in agricultural fields.